The Effects of a Wearable Sensory Prosthesis on Gait and Balance Function After 10 Weeks of Use in Persons With Peripheral Neuropathy and High Fall Risk – The walk2Wellness Trial - Oddsson, Lars I. E.; Bisson, Teresa; Cohen, Helen S.; Jacobs, Laura; Khoshnoodi, Mohammad; Kung, Doris; Lipsitz, Lewis A.; Manor, Brad; McCracken, Patricia; Rumsey, Yvonne; Wrisley, Diane M.; Koehler-McNicholas, Sara R. (Frontiers in aging neuroscience, 2020)
Sensory peripheral neuropathy (PN) is associated with gait, balance problems and high fall risk. The walk2Wellness trial investigates effects of long-term, home-based daily use of a wearable sensory prosthesis on gait function, balance, quality of life and fall rates in PN patients. The device (Walkasins , RxFunction Inc., MN, United States) partially substitutes lost nerve function related to plantar sensation providing directional tactile cues reflecting plantar pressure measurements during standing and walking. We tested the null hypothesis that the Functional Gait Assessment (FGA) score would remain unchanged after 10 weeks of use. Participants had PN with lost plantar sensation, gait and balance problems, an FGA score < 23 (high fall risk), and ability to sense tactile stimuli above the ankle. Clinical outcomes included FGA, Gait Speed, Timed Up&Go (TUG) and 4-Stage Balance Test. Patient-reported outcomes included Activities-Specific Balance Confidence (ABC) scale, Vestibular Disorders Activities of Daily Living Scale, PROMIS participation and satisfaction scores, pain rating, and falls. Evaluations were performed at baseline and after 2, 6, and 10 weeks. Subjects were not made aware of changes in outcomes. No additional balance interventions were allowed. Forty-five participants of 52 enrolled across four sites completed in-clinic assessments. FGA scores improved from 15.0 to 19.1 ( < 0.0001), normal and fast gait speed from 0.86 m/s to 0.95 m/s ( < 0.0001) and 1.24 m/s to 1.33 m/s ( = 0.002), respectively, and TUG from 13.8 s to 12.5 s ( = 0.012). Four-Stage Balance Test did not improve. Several patient-reported outcomes were normal at baseline and remained largely unchanged. Interestingly, subjects with baseline ABC scores lower than 67% (high fall risk cut-off) increased their ABC scores (49.9% to 59.3%, = 0.01), whereas subjects with ABC scores above 67% showed a decrease (76.6% to 71.8%, = 0.019). Subjects who reported falls in the prior 6 months ( = 25) showed a decrease in the number of fall-risk factors (5.1 to 4.3, = 0.023) and a decrease in fall rate (13.8 to 7.4 falls/1000 days, = 0.014). Four pre-study non-fallers ( = 20) fell during the 10 weeks. A wearable sensory prosthesis presents a new way to treat gait and balance problems and manage falls in high fall-risk patients with PN. ClinicalTrials.gov (#NCT03538756).